2021
DOI: 10.1016/j.appet.2021.105325
|View full text |Cite
|
Sign up to set email alerts
|

The relation between stimulated salivary flow and the temporal consumption experience of a liquid oral nutritional supplement

Abstract: Use of oral nutritional supplements (ONS) in undernourished patients has proven clinical benefits, but this can be hampered by low adherence due to poor experience of palatability. Many patients, particularly older patients, experience hyposalivation which can cause taste changes and reduce the enjoyment of foods. The aim of this study was to investigate differences in the temporal consumption experience (comprising sensory perception, in-mouth aroma release and subjective appetite) of a clinically relevant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Therefore, future work could focus on determining an exact JND threshold for whey protein derived mouthdrying and to achieve this both optimising protein level progression and the number of samples is needed. It should also be noted that our study was unable to collect saliva samples (due to the ongoing COVID-19 pandemic) and differences in saliva flow have recently been correlated with mouthdrying build up in ONS (Lester et al, 2021). Therefore, such differences in mouthdrying sensitivity may relate to saliva flow groups; however, this needs further proof in older adult populations and using balanced saliva flow groupings.…”
Section: Mouthdrying Just-noticeable Difference (Jnd)mentioning
confidence: 89%
“…Therefore, future work could focus on determining an exact JND threshold for whey protein derived mouthdrying and to achieve this both optimising protein level progression and the number of samples is needed. It should also be noted that our study was unable to collect saliva samples (due to the ongoing COVID-19 pandemic) and differences in saliva flow have recently been correlated with mouthdrying build up in ONS (Lester et al, 2021). Therefore, such differences in mouthdrying sensitivity may relate to saliva flow groups; however, this needs further proof in older adult populations and using balanced saliva flow groupings.…”
Section: Mouthdrying Just-noticeable Difference (Jnd)mentioning
confidence: 89%
“…Older adults appear more sensitive to the mouth drying sensation elicited by milk proteins than younger adults (90) possibly due to reduced salivary flow rates, which occurs with age, disease and medication use (46). Lester et al (58) recently detected a greater build-up of mouth drying during multiple sips of ONS for a group of healthy younger adults with a low saliva flow rate, compared to medium and high saliva flow rate groups.…”
Section: Mouth Dryingmentioning
confidence: 99%
“…Impairments in the older consumer's sensory abilities, which can occur with ageing, disease state, and medication use, likely distort both orthonasal and retronasal perception of aroma. One recent study has found an association between a lower stimulated saliva flow rate, greater in-mouth aroma release and a higher aftertaste perception during the consumption of a commonly prescribed ONS (58), which may have adversely affected appetite.…”
Section: Aroma Compoundsmentioning
confidence: 99%
“…Therefore, experiential marketing activities can enhance the consumption emotion of tourists in cultural tourism blocks (Lo and Wu, 2014;Rather and Hollebeek, 2020;. Jinan's catering should be standardized and hygienic, so that tourists' taste buds can The influence of consumption emotion on revisit intention is not significant, and the mediating effect of experiential marketing on revisit intention through consumption emotion is not significant (same as Derbaix and Pham, 1991;Ladhari, 2007;Rather, 2017;Lester et al, 2021). This study found that the mediating role played by tourists' consumption emotion in cultural tourism cities is not significant compared to that of tourism factories (Liu et al, 2021), when controlling for experiential marketing; is different from the mediating role played by experiential marketing in the retail industry (such as bicycle and car sales industry); and has no significant influence on revisit intentions (Han et al, 2010;Hou et al, 2013;Lee and Lee, 2016;Köchling, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption emotion generated by each tourist in the travel process will directly affect the tourists' consumption behavior and the willingness of secondary consumption. Holbrook MB studied the mediating role of emotion in the game product experience process (Lester et al, 2021 ). Oliver detected the emotions of customers when enjoying service packages (Mano et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%